Barriers to the influence of evidence on policy: Are politicians the problem?. (June 2013) - MacGregor, Susanne
<x xml:space="preserve">Abstract</x> This article is an analytic commentary which focuses on how politicians in the UK view the drugs problem and the relative influence on them of values and evidence. It draws on a wider qualitative case study of the contemporary British drugs problem and policies. The context is one where over-arching narratives play a dominant role and in this the mass media have been shown to be important. Politicians rarely challenge these narratives. Many see drugs as a toxic issue, one best avoided. Where drugs have appeared on the political agenda, the issue has been used as a weapon in a political game. Scientific evidence and calm appraisal have been subordinated to electoral concerns.